2010
DOI: 10.1289/ehp.0901492
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Depression and Its Association with Pesticide Exposure across the Agricultural Season among Latino Farmworkers in North Carolina

Abstract: BackgroundFarmworkers can be exposed to a wide variety of pesticides. Assessing cholinesterase activity over time can be used to monitor exposure to organophosphorus and carbamate pesticides.ObjectivesThe goal of this study was to document patterns and variation in cholinesterase levels across the agricultural season (May–August) among field-workers, and to explore the association of cholinesterase depression with pesticide exposure across the agricultural season.MethodsDried blood samples collected from 231 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 33 publications
0
48
2
4
Order By: Relevance
“…An additional limitation often encountered by past studies was the absence of established baseline AChE and BChE levels. A recent adult study examining the variation of ChE levels among OP pesticides and carbamate-exposed fieldworkers could not establish any baseline AChE/BChE due to the mobility of the migrant study population 40. Another Egyptian adolescent study also reported a greater reduction of AChE activity among pesticide applicators compared to controls 20 21.…”
Section: Discussionmentioning
confidence: 96%
“…An additional limitation often encountered by past studies was the absence of established baseline AChE and BChE levels. A recent adult study examining the variation of ChE levels among OP pesticides and carbamate-exposed fieldworkers could not establish any baseline AChE/BChE due to the mobility of the migrant study population 40. Another Egyptian adolescent study also reported a greater reduction of AChE activity among pesticide applicators compared to controls 20 21.…”
Section: Discussionmentioning
confidence: 96%
“…We showed that cholinesterase activity was significantly lower later in the summer and that depressions in cholinesterase activity were related to the number of different organophosphorus and carbamate pesticide metabolites detected in urine. 15 That study had several shortcomings, including cholinesterase data from just a single year; lack of a comparison group; no information on potential residential pesticide exposure; and cholinesterase obtained from dried whole blood samples, preventing differentiation of acetylcholinesterase and butyrylcholinesterase activities. The current study was designed to remedy these shortcomings to more definitively assess evidence of work-related exposure to cholinesterase-inhibiting pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…It needs to be remarked, though, that sensitivity is rather limited and ideally one should know an individual's enzyme activity prior to exposure, with only considerable intoxications resulting in a significant decrease in enzyme activity. Yet, multiple other publications have shown the potential to use (dried) blood and plasma spots for monitoring cholinesterase activity, primarily for occupational surveillance of exposed workers (Augustinsson and Holmstedt, 1965, Holmstedt and Oudart, 1966, Collombel and Perrot, 1970, Oudart and Holmstedt, 1970, Augustinsson et al, 1978, Eriksson and Faijersson, 1980, Rhyanen et al, 1984, Hilborn and Padilla, 2004, Quandt et al, 2010. Several of the DBS applications for monitoring environmental contaminants are discussed more into depth below.…”
Section: Analysis Of Environmental Contaminantsmentioning
confidence: 99%
“…LC-MS/MS GC-MS Jantos and Skopp, 2011;Jantos et al, 2011b;Lauer et al, 2011 Langel et al, Henderson et al, 1993Henderson et al, 1997Mercolini et al, 2010Sosnoff et al, 1996Alfazil and Anderson, 2008;Lauer et al, 2011Langel et al, 2011 Benzodiazepines LC-MS/MS GC-MS Alfazil and Anderson, 2008;Havard et al, 2010;Thomas et al, 2010;Jantos and Skopp, 2011;Lauer et al, 2011 Langel et Boy et al, 2008;Thomas et al, 2010;Marin et al, 2010;Clavijo et al, 2011a;Jantos et al, 2011a;Lauer et al, 2011Langel et al, 2011 Buprenorphine and metabolites Thomas et al, 2010;Marin et al, 2010, Lauer et al, 2011 Heilbronn, 1953;Augustinsson and Heimburger, 1953;Augustinsson and Holmstedt, 1965;Holmstedt and Oudart, 1966;Collombel and Perrot, 1970;Oudart and Holmstedt, 1970;Augustinsson et al, 1978;Eriksson and Faijersson, 1980;Rhyanen et al, 1984;Hilborn and Padilla, 2004;Trudeau et al, 2007;Quandt et al, 2010 Table 1. Overview of the analytes discussed in this review, with referral to the utilized analytical techniques.…”
Section: Analytementioning
confidence: 99%